Content-Management-Systeme in Fachverlagen: Ergebnisse einer empirischen Erhebung - Svenja Hagenhoff (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2014)
– The development and differentiation of devices and technologies (tablets, smart-phones) which are suitable for reception of contents has led to cross-media distribution of contents by the publishing houses. Once created, content is made available parallel in different media channels electronically but also in printed form, an idea which is known as cross media publishing. In order to be able to produce media for reading in different variants, high-performance IT-supported processes are needed that allow an automated generation of different variants. Content Management Systems (CMS) fulfill this purpose. In research, the topic is already covered since the early 2000s, when XML technology emerged. This raises the question of whether cross-media publishing strategies are already being practiced in the publishing practice, and if so, if they are supported by suitable software systems. Discussions with representatives of the industry gave rise to the assumption that cross-media publishing is still not widespread. Where already content through different channels is distributed, system solutions are not yet a standard. Information on the actual use of these systems in publishing houses is missing. This information gap is to be reduced with this empirical study. The focus of the investigation is on German-language special interest publishers.
urn:nbn:de:bvb:29-opus4-41954
Keywords: 650; Cross Media Publishing; Content Management; Medienwirtschaft; Fachverlag; Verlagswesen; Medienmanagement; Content Management; Deutschland